Management of the Socio-Economic Potential of Rural Areas: Functional Model of Farming Development - Irina V. MINAKOVA; Tatyana N. BUKREEVA; Yuriy V. BUKHVOSTOV; Tatiana S. KRAVCHENKO; Nadezhda A. SUKHOCHEVA (Communications of International Proceedings, 2021)
Russian authorities of different levels have continually highlighted the role and economic significance of small businesses in ensuring the competitiveness of the agro-industrial complex and the village revival. The purpose of the study is to create a farm development model, focusing on the social-economic potential of a rural area. The authors have analysed the trends in agricultural production of the farming sector and identified the issues in labour force development in rural areas. Foreign countries give preference to small businesses, focusing on family farms, which are very efficient due to their strong motivation and high productivity. Farming accounts for about 90% of the agriculture sector of the USA, Germany and Finland. In 2019, in the total volume of crop production in the world, US farmers produced 463.7 million tons, Chinese farmers – 210.4 million tons, Russian farmers – 53.7 million tons, and German farmers – 42.2 million tons, despite the facts that the contribution of agricultural products to GDP of those countries accounts for a mere 0.6-4.6%, and the share of rural population to total number of population in the above-mentioned countries is 18-41%. As a result, we have determined the need to develop the village socio-economic structure in the close relationship and interaction of society, business and the state, and introduced a functional model of the socio-economic development of rural areas through peasant farming. The model is based on the achievement of objectives of rural development through the productivity of small agribusinesses, which impacts on the socio-economic potential of rural areas. The article proposes the measures to attract young professionals to agribusiness and implement a resettlement policy. Successful achievement of the objectives will allow preserving the labour potential of rural areas and improving the current state of the agricultural sector through state support for the farming sector, which in turn contributes to an increase in self-employment of local residents, an increase in labour productivity and income growth of rural populations.
Keywords: Rural Areas; Socio-Economic Potential; Farming Development; Agribusiness; Agricultural Sector.